2016
DOI: 10.1108/ijmhsc-03-2015-0008
|View full text |Cite
|
Sign up to set email alerts
|

Falling through the cracks? An analysis of health and safety resources for migrant workers in Australia

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…This is particularly relevant for this group as one's status as a migrant and/or with precarious status, and/or racialized identity and/or working in agriculture have been shown to be correlated with poorer working conditions (44, 64). Kosny and Allen (65) found that migrant agricultural workers in Australia were not properly informed about their roles in injury prevention and workplace safety, being solely responsible for finding resources, and often, not being aware of any. Other research reports limited use of personal protective equipment (PPE) within the farm setting among this population, resulting in likely significant pesticide exposure (66) that training was often considered inconsistent or insufficient among MAWs.…”
Section: Living and Working Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is particularly relevant for this group as one's status as a migrant and/or with precarious status, and/or racialized identity and/or working in agriculture have been shown to be correlated with poorer working conditions (44, 64). Kosny and Allen (65) found that migrant agricultural workers in Australia were not properly informed about their roles in injury prevention and workplace safety, being solely responsible for finding resources, and often, not being aware of any. Other research reports limited use of personal protective equipment (PPE) within the farm setting among this population, resulting in likely significant pesticide exposure (66) that training was often considered inconsistent or insufficient among MAWs.…”
Section: Living and Working Conditionsmentioning
confidence: 99%
“…Language barriers impacted MAWs' ability to seek support (2,13,41,42,60,63,74,75). Along with a lack of formal education and inaccessibility of safety materials, language barriers also created higher risks of occupational injuries (42,63,65). Language barriers also presented a challenge for accessing quality healthcare (2,74,(76)(77)(78).…”
Section: Facilitators/barriers To Navigating Services and Supportsmentioning
confidence: 99%
See 1 more Smart Citation